Application of the natural orifice specimen extraction surgery I-type E method combined with 3D laparoscopy in sphincter-preserving surgery of low rectal cancer - Bo, Jiang; Liu, Maoxi; Xingyu, Guo; Wenqi, Bai (Frontiers in Surgery, 2022)
Purpose Analysis of the clinical efficacy of the application of the NOSES I-type E method combined with 3D laparoscopy in sphincter-preserving surgery of low rectal cancer. Method A retrospective analysis of 109 patients who underwent laparoscopic low rectal cancer surgery for anus preservation without preventive stoma admitted to the Department of Colorectal Surgery in Shanxi Provincial Cancer Hospital between January 2017 and May 2019. The 109 cases comprised 52 cases treated with the NOSES I-type E method and 57 cases treated with the Dixon method.In the NOSES I-type E group,25cases underwent 3D laparoscopic surgery (group A) and 27 cases underwent 2D laparoscopic surgery (group B).The general clinical data,perioperative indicators,three-day postoperative pain score, postoperative pathological conditions, complications, return visit to assess the 1-year postoperative anal function, 3-year local recurrence and distant metastasis, and survival were compared among the groups. Result The distance between the tumor and the anal verge was significantly different between NOSES I-type E group and the Dixon group (P< 0.05).The exhaust time, eating time,drainage tube removal time,hospitalization costs, hospitalization time,and the number of days of analgesic administration were significantly different between NOSES I-type E group and the Dixon group (P<0.05).There were significant differences in difficulty urinating between group A and B (P<0.05).Anastomotic leakage in NOSES I-type E group were significantly lower than those in the Dixon group (P<0.05).Anal stenosis,rectal Prolapse and colon retraction in NOSES I-type E group were significantly higher than those in Dixon group(P< 0.05).Anastomotic bleeding in Dixon group occurred in higher frequency than in NOSES I-type E group(P< 0.05).The pain scores of patients in NOSES I-type E group in the first three days after operation were significantly lower than those in Dixon group(P<0.05).There were no significant differences in postoperative pathology, 1-year postoperative anal function score, 3-year recurrence rate and overall survival rate among the groups (P> 0.05). Conclusion The NOSES I-type E method is a safe and effective sphincter-preserving operation for low rectal cancer and its combination with 3D laparoscopy may have better neurological protection which is worth of clinical application.